Evaluasi Sinkronisasi Alat Gali Muat dan Alat Angkut Pengupasan Overburden di PT XXY - Yopan Yopan; Ahmad Husni; Rodiyah Nursani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study evaluates the operational synchronization between loading and hauling equipment in overburden stripping activities at PT XXY, South Sumatra, using an empirical field-based approach conducted from April to June 2025. The system architecture consists of one excavator and several Off Highway Trucks operating within a single active mining front. Primary data were obtained through direct cycle time measurements of at least 30 representative cycles per unit, supported by secondary technical parameters including bucket capacity, swell factor, hauling distance, and effective working hours. Productivity analysis indicates an initial output of 367.81 BCM/hour with a match factor of 0.96, reflecting capacity imbalance and excavator waiting time. Simulation of fleet adjustment to eight hauling units increased productivity to 420.36 BCM/hour and improved system balance while reducing specific fuel consumption from 0.41 to 0.37 liter/BCM. Efficiency evaluation demonstrates that synchronization directly influences operational utilization, energy intensity, and production target achievement.